การวัดความเสี่ยงของพอร์ตโฟลิโอตราสารหนี้ด้วยวิธีคอปปูลามูลค่าความเสี่ยงและวิธีคอปปูลาค่าเฉลี่ยความเสียหายส่วนเกิน - กุสุมา โคจร (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this research, we aim to measure the risk of investment in a bond portfolio from one of insurance companies by using data on investments in bond securities and historical interpolated zero coupon yields from ThailBMA. We use copula to find a joint distribution function and time to maturity of bond yield. And then we also use Value at Risk (VaR) and Expected Shortfall (ES) to determine the level of risk that may occur to the portfolio in bond. Moreover, we compare the accuracy of risk tolerance between copula VaR and normality VaR. The result shows that the yield of bond is not a normal distribution, and the distribution pattern of the actual bond yield is Logistic distribution. However, the result of finding the Validity Testing by Bancktesting show that Copula VaR and Normality VaR are very similar. Therefore we can use them to measure the level of risk more effectively.